Pengaruh Konflik Kerja dan Motivasi Kerja terhadap Kinerja Karyawan - Zafarina, Shabrina; Frianto, Agus (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research aims to examine and analyze the impact of a work conflict and work motivation on employee performance. The research method is quantitative research. The sample in this study is 40 employees. The statistical analysis used in this study is the validity and reliability test, classical assumption test, and multiple linear tests. Data processing using SPSS software version 18. This study shows that work conflict has a negative and insignificant effect on employee performance and work motivation has a positive and significant effect on employee performance. This study implies that work conflicts that occur in employees in the company do not make the level of performance decrease; besides, the company has succeeded in implementing work motivation because the higher the motivation of employees, the higher the performance for the company.